Anti-quorum Sensing and Antimicrobial Effect of Mediterranean Plant Essential Oils Against Phytopathogenic Bacteria - Camele, Ippolito; Elshafie, Hazem S.; Caputo, Lucia; De Feo, Vincenzo (Frontiers in Microbiology, 2019)
Essential oils (EOs) are one of the most interesting natural products extracted from different aromatic plants. For centuries, EOs have been considered an essential part of the traditional pharmacopeia. Many plant EOs have been reported as possible effective alternatives for commercial pesticides, and their single constituents have been used efficiently in food preservation for their promising anti-QS activity against several food pathogenic microorganisms. The current mini review gives a general overview over the microbicide effect as well as anti-quorum sensing and the anti-biofilm formation of some common plant EOs, especially those of Lamiaceae and Verbanaceae families; these are commonly grown in the Mediterranean region and are effective against some serious food phytopathogenic bacteria.